Quantifying Biogenic Versus Detrital Carbonates on Marine Shelf: An Isotopic Approach - Pasquier, V.; Revillon, S.; Leroux, E.; Molliex, S.; Mocochain, L.; Rabineau, M. (Frontiers in Earth Science, 2019)
The terrigenous sedimentary budget of passive margin records variations in past sedimentary fluxes, and thus can be used to infer past variations of Earth surface deformation processes, or climate change. Accurate estimates of sediment fluxes over various times scale and space-scale are therefore crucial. Traditionally, offshore sediment sequence volumes take into account only siliciclastic accumulation, the carbonate fraction being considered only as in-situ production (i.e. CaCO3). Here we propose a new geochemical methodology to decipher and quantify the amount of detrital carbonates in comparison to in-situ produced biogenic carbonates. This isotopic approach enables taking into account the export of detrital carbonates, and investigating its effect on sediment budgets. This study, located in the Gulf of Lion, is based on a 300 m long sediment borehole located near the shelf break and covering the last 500 000 years (i.e. 5 glacial-interglacial periods). 86Sr/87Sr isotopic data (0.70809 to 0.70858) are significantly less radiogenic than modern seawater (i.e. 0.7092) and show fluctuations in agreement with stratigraphic and climatic variations. These results suggest an unsuspected high export of detrital carbonates from the catchment area during both glacial (between 55 to 85% of the sedimentary carbonate fraction) and interglacial (between 30 to 50%) conditions. Thus, not only do detrital carbonate fluxes need to be factored into sediment flux calculations, these results suggest that detrital carbonate components could potentially have a strong influence on carbonate 86Sr/87Sr ratios when not obtained from microdrilled biogenic carbonates, such as the entirety of the Precambrian Sr chemostratigraphic record.